Structure and RNA-binding properties of the Type III-A CRISPR-associated protein Csm3 - Hrle, Ajla (Landes Bioscience, 2013)
The prokaryotic adaptive immune system is based on the incorporation of genome fragments of invading viral genetic elements into clusters of regulatory interspaced short palindromic repeats (CRISPRs). The CRISPR loci are transcribed and processed into crRNAs, which are then used to target the invading nucleic acid for degradation. The large family of CRISPR-associated (Cas) proteins mediates this interference response. We have characterized Methanopyrus kandleri Csm3, a protein of the type III-A CRISPR-Cas complex. The 2.4 Å resolution crystal structure shows an elaborate four-domain fold organized around a core RRM-like domain. The overall architecture highlights the structural homology to Cas7, the Cas protein that forms the backbone of type I interference complexes. Csm3 binds unstructured RNAs in a sequence non-specific manner, suggesting that it interacts with the variable spacer sequence of the crRNA. The structural and biochemical data provide insights into the similarities and differences in this group of Cas proteins.